Parental Role Models and Gender Norms Subversion: The Case of Jackie Kay’s “Trumpet” - Kaličanin, Milena M.; Mitić, Kristina S. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
The article discusses the complexity of gender identity in Jackie Kay’s novel “Trumpet” (1998). The theoretical framework provides a brief overview of the social construction of gender based on the gender binary, which categorizes gender as either male or female, on the basis of the sex assigned at birth. The concepts of transgender and non-binary gender identities are introduced and problematized in the first segment of the research, drawing on the critical insights of Stryker, Butler, Wittig, Foucault, Althusser, and others. The authors examine the position of marginalized individuals whose gender is neither female nor male, but both, and inspect how such individuals, who represent non-binary gender or gender fluidity, are treated in contemporary society. The article explores Jackie Kay’s critical stances on gender identity, compulsory heterosexuality, gender inequality, and oppression. It also argues that subversion of gender norms can be accomplished through the combined impact of parental role models and art, in particular jazz music.